1994
DOI: 10.2118/21780-pa
|View full text |Cite
|
Sign up to set email alerts
|

Steam-Foam Mechanistic Field Trial in the Midway-Sunset Field

Abstract: A one-pattern, steam-foam mechanistic field trial was conducted in Section 26C of the Midway-Sunset field (upper Monarch sand). The test objectives were (1) to understand the mechanisms of steam diversion caused by foam under reservoir conditions, (2) to establish whether foam can exist in-depth away from the injection well, and (3) to measure incremental oil that can be attributed to foam. Surfactant was injected with steam and nitrogen continuously, and bottomhole injection pressure (BIHP) increased from 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(45 citation statements)
references
References 9 publications
4
41
0
Order By: Relevance
“…This mobilization pressure drop is important because an extremely high mobilization pressure gradient limits the success of foam in EOR applications. If the required mobilization pressure gradient is too large, the foam is not an effective drive fluid for EOR, because there is a limit to what injection pressures can be used in the field, especially in places where the well-to-well distance is very long (Rossen and Gauglitz, 1990;Friedmann et aL, 1991). Different predictions for required mobilization pressure drop are presented in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…This mobilization pressure drop is important because an extremely high mobilization pressure gradient limits the success of foam in EOR applications. If the required mobilization pressure gradient is too large, the foam is not an effective drive fluid for EOR, because there is a limit to what injection pressures can be used in the field, especially in places where the well-to-well distance is very long (Rossen and Gauglitz, 1990;Friedmann et aL, 1991). Different predictions for required mobilization pressure drop are presented in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…For only curvature-driven rearrangement of liquid (Le., Cam = 0), a square pore with a constriction to body ratio greater than about 0. 4 does not snap-off. The pore is starved for liquid even though the static Roof criterion indicates that snap-off may occur.…”
Section: Liquid Accumxjutionmentioning
confidence: 96%
“…Gas and surfactant solution can form multiple local-equilibrium (LE) states for the same injection conditions. It is commonly observed that at low superficial velocity there is "weak" or "coarse" foam, with a modest reduction in gas mobility (Ransohoff and Radke 1988;Rossen and Gauglitz 1990;Friedmann et al 1991Friedmann et al , 1994Tanzil et al 2002;Gauglitz et al 2002). Creation of strong foam is triggered by an increase in superficial velocity or pressure gradient; thereafter injection rate can be returned to the lower values and the strong foam remains at velocities for which weak foam was previously observed.…”
Section: Introductionmentioning
confidence: 94%